Kajian Desain Inklusif “Grey Room” untuk Siswa dengan ADHD: Studi Kasus SD Tamansari 1 Yogyakarta - Diwangkoro, Raden Bagus Budho; Utama, Aditya Noor Hadhy; Sholihah, Arif Budi (INKLUSI, 2024)
Inclusion rooms for students with Attention-Deficit Hyperactivity Disorder (ADHD) in schools are urgently needed to overcome and reduce symptoms of hyperactivity. This study aims to examine the inclusive design of the Grey Room, so that a reference can be obtained for designing appropriate private spaces for children with ADHD at school. This research method uses a comparative qualitative method between the Grey Room with the criteria of several theories regarding the design of the Grey Room for children with ADHD by taking a case study at SD Tamansari 1 Yogyakarta. It was found that the Grey Room is a combination of seclusion room and resource room. The Grey Room is designed with reference to some of the criteria for a seclusion room but is also used as a resource room. There are differences between the criteria, design and utilization so that a deeper study is needed regarding the Grey Room. Ruang inklusi untuk siswa dengan Attention-Deficit Hyperactivity Disorder (ADHD) di sekolah sangat dibutuhkan untuk mengatasi dan mengurangi gejala hiperaktivitas. Penelitian ini bertujuan untuk menelaah desain inklusif Grey Room, sehingga bisa didapatkan acuan untuk merancang ruang privat yang tepat untuk anak dengan ADHD di sekolah. Metode penelitian ini menggunakan metode kualitatif komparatif antara Grey Room dengan kriteria dari beberapa teori mengenai desain Grey Room untuk anak dengan ADHD dengan mengambil studi kasus pada SD Tamansari 1 Yogyakarta. Didapatkan bahwa Grey Room merupakan kombinasi antara seclusion room dan resource room. Grey Room didesain dengan mengacu pada sebagian kriteria seclusion room tetapi dimanfaatkan juga sebagai resource room. Terdapat perbedaan antara kriteria, desain dan pemanfaatan sehingga diperlukan telaah yang lebih dalam mengenai Grey Room.